Do Stock Dividends Generate Abnormal Returns? - Torgal, Kishan (2009)
In this paper I have studied and understood the concepts of stock dividends, stock splits and the announcement effects and the effective day effects by using the standard event studies methodology which measures the significance of the abnormal returns. The previous studies have significant positive abnormal returns. In my results its shown that the as there is some significant abnormal returns which are connected with the announcement and effective day of the stock splits but it changes after some days at it has been found some significant abnormal returns.